Lactoferrin Decreases the Intestinal Inflammation Triggered by a Soybean Meal-Based Diet in Zebrafish. (10th May 2016) - Ulloa, Pilar E.; Solís, Camila J.; De la Paz, Javiera F.; Alaurent, Trevor G. S.; Caruffo, Mario; Hernández, Adrián J.; Dantagnan, Patricio; Feijóo, Carmen G.
Abstract : Intestinal inflammation is a harmful condition in fish that can be triggered by the ingestion of soybean meal. Due to the positive costs-benefits ratio of including soybean meal in farmed fish diets, identifying additives with intestinal anti-inflammatory effects could contribute to solving the issues caused by this plant protein. This study evaluated the effect of incorporating lactoferrin (LF) into a soybean meal-based diet on intestinal inflammation in zebrafish. Larvae were fed with diets containing 50% soybean meal (50SBM) or 50SBM supplemented with LF to 0.5, 1, 1.5 g/kg (50SBM+LF0.5; 50SBM+LF1.0; 50SBM+LF1.5). The 50SBM+LF1.5 diet was the most efficient and larvae had a reduced number of neutrophils in the intestine compared with 50SBM larvae and an indistinguishable number compared with control larvae. Likewise, the transcription of genes involved in neutrophil migration and intestinal mucosal barrier functions ( mmp9, muc2.2, and β-def-1 ) were increased in 50SBM larvae but were normally expressed in 50SBM+LF1.5 larvae. To determine the influence of intestinal inflammation on the general immune response, larvae were challenged with Edwardsiella tarda . Larvae with intestinal inflammation had increased mortality rate compared to control larvae. Importantly, 50SBM+LF1.5 larvae had a mortality rate lower than control larvae. These results demonstrate that LF displays a dual effect in zebrafish, acting as an intestinal anti-inflammatory agent and improving performance against bacterial infection.